Genetic and biochemical insights into siderophore biosynthesis in the marine fish pathogen Tenacibaculum maritimum - M. Pilar Escribano; Lucía Ageitos; Miguel Balado; Larissa Buedenbender; Jaime Rodríguez; Carlos Jiménez; Beatriz Magariños; Manuel L. Lemos (Scientific Reports)
Abstract Siderophore production is a key fitness trait for bacteria, particularly in iron-limited environments such as marine ecosystems and host tissues. In this study, we identify the tenABECDC2D2hp1-4 gene cluster as responsible for siderophore biosynthesis in Tenacibaculum maritimum, confirmed through genome analysis and a tenCD-inactivated mutant. This cluster, highly similar to the desferrioxamine biosynthesis system in Streptomyces coelicolor, features a unique tenCD duplication/fusion, essential for siderophore formation. Additionally, accessory genes (hp1-4) encode functions such as nitroreductase and N-acetyltransferase, likely contributing to siderophore diversification. LC/MS analysis of T. maritimum cultures revealed the production of 20 amphiphilic, acylated desferrioxamine-like siderophores. These findings provide new insights into the genetic and metabolic versatility of marine pathogens in iron acquisition.